Research on the construction and operation mode of urban cellular vehicle to everything - Zhenting CHANG; Zhendong XIE; Zhiguo DONG (Dianxin kexue)
With the support of national policies,cities are actively promoting the development of cellular vehicle to everything industry.Combined with the actual situation of cellular vehicle to everything industry and the development of “one city,one network and one platform” in the future,the main participants,construction and operation contents that affect the project were analyzed,various construction and operation modes of cellular vehicle to everything project were summarized and analyzed,and the next development was prospected.